Soil Phosphorus Bioavailability and Soybean Grain Yield Impaired by Ruzigrass - Almeida, Danilo S.; Rocha, Kassiano F.; Souza, Murilo; Delai, Lucas B.; Rosolem, Ciro A. (Agronomy journal, 2018)
Core Ideas There have been suggestions that ruzigrass increases soil P availability.Ruzigrass was grown in rotation with soybean from 2012 to 2016.The observed effect was opposite from the expected under long‐term field conditions.Crop rotation with ruzigrass resulted in a lower soybean grain yield than fallow. Under no‐till farming systems, the use of crop rotations with species adapted to low P soils may enhance soil P availability through P cycling. Growing ruzigrass [Urochloa ruziziensis (R. Germ. and C.M. Evrard) Morrone and Zuloaga] as a cover crop has shown to increase resin extractable P in soils. However, it is not clear how the next crop responds to ruzigrass in the long term. The objective of this study was to evaluate the long‐term effect of growing ruzigrass on soil P availability to soybean [Glycine max (L.) Merr.]. The evaluations were performed over 5 yr on a ruzigrass–soybean crop rotation, in Botucatu, Brazil. The treatments were P rates (0, 13, and 26 kg ha−) applied to soybean seed furrows, and ruzigrass or fallow during the off‐season. Soil samples were taken after ruzigrass desiccation, and soil P was extracted with resin (Presin). The use of ruzigrass increased soil organic matter (SOM) by approximately 20% compared with fallow, regardless of P rates, and increased Presin concentration in the 0‐ to 10‐cm soil depth by approximately 10% with 26 kg ha− of P. Surprisingly, grain yield and soybean leaf P concentration were lower after ruzigrass compared with fallow. Resin seemed to be unsuitable to compare P availability in different cropping systems. In the long‐term, growing ruzigrass as a cover crop in the off‐season decreases P and N availability to soybean, eventually decreasing soybean grain yield. Further studies are needed to understand the mechanisms involved in this unexpected soybean response when cropped in rotation with ruzigrass.